Complete Denture Treatment With a Flat Ridge Using Semi-adjustable Articulator - Herdianti, Nur Cecilia; Soekobagiono, Soekobagiono; Dahlan, Agus (Indonesian Journal of Dental Medicine, 2018)
Background: Complete denture is a removable denture replacing all the missing teeth and tissue in the upper jaw and lower jaw. The purpose of making complete denture is to improve the function of chewing, aesthetic functions and maintaining patient's oral health. Complete edentulous ridge will causes resorption, until it become flat. A flat ridge is associated with difficulties in providing successful dentures. Purpose: This case report aims to reported the treatment of complete edentulous maxillary and mandibular with a flat ridge using semi-adjustable articulator. Case(s): A 63-year-old male patient visited the Prosthodontic Clinic of Dentistry Faculty, Airlangga University with complete edentulous maxillary and mandibular, also flat ridge in his mandibular.  Case Management: This case is using semi-adjustable articulator (Stratos 300). Some accessories in Stratos 300 were used in this case, such as centric tray to help determine the height of bite, gnathometer M to help the process of functional impression and bite block, also tooth arrangement with 2D templates. Conclusion: The use of semi-adjustable articulator (Stratos 300) could restore stomatognathic function in accordance with patient's condition.